Utilization of fucoidan extract from brown algaes as antibacteria on tooth: Pemanfaatan ekstrak fucoidan dari alga cokelat sebagai antibakteri pada gigi - Rezky Pangestu Aji; Andi Nirmala Sari; Ahmad Rafiesa Guna; Lenni Indriani; Asmawati (Makassar Dental Journal, 2023)
Fucoidans are sulfated polysaccharides found in marine algae and have many benefits, including antitumor effects, increasing apoptosis of cancer cells, antiviral, anti-inflammatory, and hypoallergenic. In oral health, several case reports have shown that creams and tablets containing fucoidan are proven to treat recurrent aphthous stomatitis and recurrent oral herpes labialis. The aim of this study was to investigate the properties of fucoidans used in oral health as antimicrobial and antibacteria. Secondary data and literature study were analyzed descriptively by presenting and comparing the results of research on the use of fucoidan extract from brown algae as an antibacterial agent for teeth. Fucoidan extract from brown algae has been proven has the ability to inhibit bacteria that cause damage to the oral cavity, Streptococcus mutans, Porphyromonas gingivalis and Fusobacterium. Four main results were obtained: fucoidans showed strong antimicrobial activity against C.albicans, S.mutans, and P.gingiva-lis; attachment is obstructed, S.mutans on bovine and porcelain teeth; exhibit COX-1 and or COX-2 inhibitory activity. It is concluded that fucoidan extract from brown algae can reduce oral pathogens and has antibacterial activity